2006
DOI: 10.1177/0165551506064397
|View full text |Cite
|
Sign up to set email alerts
|

How influential is Brooks’ Law? A longitudinal citation context analysis of Frederick Brooks’ The Mythical Man-Month

Abstract: Citation context analysis is used to demonstrate the diversity of concept symbols that a book-length publication can represent and the diffusion of influence of these concepts over time and across scholarly disciplines. A content analysis of 574 citation contexts from 497 journal articles citing an edition of Frederick P. Brooks, Jr's The Mythical Man-Month (MMM) over the period 1975-1999 showed that MMM represents a variety of different concepts and is cited in a wide range of subject areas. Over time, a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 42 publications
(75 reference statements)
1
44
0
Order By: Relevance
“…What it means is that when we work with textual and symbolic material quantitatively versus qualitatively there is potential to obtain different types and levels of insight (e.g., see Zuccala et al 2014). In fact, the history of 'citation-ology' (i.e., the study of referencing and citation behavior) has already demonstrated that what we learn from approaching the highly textual, contextual, and symbolic citation, using a qualitative method of investigation can differ greatly than when we approach the same citation using a quantitative method of analysis (Bornmann and Daniel 2008;Brooks 1985;McCain 2006;Small 1978). When we grapple with measuring products and citations from humanistic research, it is less important; therefore, to distinguish data for specific forms of 'treatment' (e.g., this data is qualitative/quantitative and that is not, so this should only be examined quantitatively/qualitatively), and more important to focus on how the data needs to be curated to effectively support a chosen method.…”
Section: Databases and Data Quality For The Sshmentioning
confidence: 99%
“…What it means is that when we work with textual and symbolic material quantitatively versus qualitatively there is potential to obtain different types and levels of insight (e.g., see Zuccala et al 2014). In fact, the history of 'citation-ology' (i.e., the study of referencing and citation behavior) has already demonstrated that what we learn from approaching the highly textual, contextual, and symbolic citation, using a qualitative method of investigation can differ greatly than when we approach the same citation using a quantitative method of analysis (Bornmann and Daniel 2008;Brooks 1985;McCain 2006;Small 1978). When we grapple with measuring products and citations from humanistic research, it is less important; therefore, to distinguish data for specific forms of 'treatment' (e.g., this data is qualitative/quantitative and that is not, so this should only be examined quantitatively/qualitatively), and more important to focus on how the data needs to be curated to effectively support a chosen method.…”
Section: Databases and Data Quality For The Sshmentioning
confidence: 99%
“…We cannot address Yalpani and Heydari's assertions as to the contributing causes of the publication and citation patterns, but our findings do confirm the patterns' existence in terms of the remarkable publication rate (which can be achieved with many small publications in journals with high acceptance rates), and the use that citing authors make of the oeuvres of chemists highly cited in Iranian chemistry publications. A citation content and context analysis (Small, 1978;McCain & Salvucci, 2006;McCain & Turner, 1989) is beyond the scope of this study but would be a natural next step in assessing how the cited authors' work-both Iranian and International-is actually deployed in the citing authors' writing. Studies of selected Iranian and International authors' Citation Images and Citation Image Makers (White, [10]) would contribute to this as well.…”
Section: Resultsmentioning
confidence: 99%
“…An example of this effect is illustrated by the study of the use and migration of Brooks' ideas on project management as published in his book The Mythical Man-Month (Brooks, 1995(Brooks, (1975) across different subject areas (McCain & Salvucci, 2006). Similar temporary shifts in interpretation are entirely possible for the concept of product modularity, and a longitudinal study of its evolution presents another fruitful future research avenue.…”
Section: Discussionmentioning
confidence: 96%